Polyp detection rate and cumulative incidence of post‐colonoscopy colorectal cancer in Germany. Issue 8 (7th December 2022) - Schwarz, Sarina; Hornschuch, Michel; Pox, Christian; Haug, Ulrike
Abstract: Studies have shown that the quality of colonoscopy influences the incidence of post‐colonoscopy colorectal cancer (PCCRC). However, data from Germany on this association are lacking. We aimed to assess cumulative incidence of PCCRC in persons undergoing colonoscopy in Germany according to the physician's polyp detection rate (PDR). Using the German Pharmacoepidemiological Research Database (GePaRD) with claims data of ~20% of the German population, we included persons with a baseline colonoscopy between 2008 and 2017 and categorized them according to the procedure at baseline (snare polypectomy, forceps polypectomy, no polypectomy). In each subgroup, we distinguished between persons examined by physicians with a PDR in the lowest quartile vs higher quartiles and described cumulative CRC incidence during follow‐up. Overall, 822 715 persons examined by 1752 physicians were included. One quarter of the physicians had a PDR ≤21.8% (lowest quartile). In all subgroups, the 5‐year cumulative CRC incidence was statistically significantly higher in persons examined by physicians with a PDR ≤21.8% vs >21.8%: It was 69% higher in persons with snare polypectomy (0.88% vs 0.52%), 87% higher in persons with forceps polypectomy (0.58% vs 0.31%), and 48% higher in persons without polypectomy at baseline (0.31% vs 0.21%). In conclusion, we found a substantially increased PCCRC risk in persons examined by physicians with a low PDR in Germany, irrespective of the baseline findings. Our study highlights the importance of a high‐quality colonoscopy to maximize the preventive effect of colonoscopy on CRC incidence. Abstract : What's new? Most post‐colonoscopy colorectal cancers (PCCRCs) are assumed to arise from missed lesions, and various criteria have been defined to assess the quality of colonoscopy. Our study uses a large German claims database to assess whether the cumulative incidence of PCCRC in persons undergoing colonoscopy in Germany differs according to their physician's polyp detection rate (PDR). The results show an inverse association between the PDR and PCCRC risk, both in persons with and without detected polyps at baseline. The study highlights the importance of high‐quality colonoscopy to maximize its preventive effect on colorectal cancer incidence.